Analysis of Letter of Credit (L/C) Payment Methods Amid Payment System Disruption - Chrisian Chrisian; Reikman D.P Aritonang (Program Studi Akuntansi FPEB UPI, 2024)
Businesses strive for efficiency in their payment methods, often considering switching from L/C to open account financing. However, L/C remains unique due to its adherence to internationally recognized rules, making it irreplaceable. The decision to use L/C involves assessing its strengths and weaknesses. The research aims to analyze the impact of bank's undertaking, access to bank financing, performance pisks, L/C transaction costs and the L/C process on corporate decisions. The study utilizes primary data gathered through questionanaires from 50 respondents and employs multiple regression analysis and classic assumption tests. The findings indicate that bank's undertaking, access to bank financing, performance risks partially have a positive effect on the decision to use L/C. However, L/C transaction costs and the L/C process partially did not have a positive effect on the decision to use L/C. When considered together, these factors significantly impact the decision to use L/C. To enhance L/C usability, the solution proposed is to reduce negatively influencing variables, including the implementation of Blockchain technology to reduce L/C transaction costs and expedite the L/C process. Keywords : access to bank financing, bank's undertaking, decision to use L/C, performance risks, L/C transaction costs, L/C process